2019
DOI: 10.1589/jpts.31.261
|View full text |Cite
|
Sign up to set email alerts
|

Particular protrusion perception arising from plantar sensory input and task guidance enhances lower limb joint dynamics during gait

Abstract: [Purpose] To assess the influence of plantar sensory input and task guidance produced by a protrusion on lower limb joint dynamics during gait by changes in muscle activity and two-dimensional motion analysis. The protrusion seals on the soles of the feet, named “Perceptual Stimulus Protrusion” were used in this study. [Participants and Methods] In this study, 40 and 42 healthy adults were recruited for muscle activity and two-dimensional analysis, respectively. In addition to walking without perceptual stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…It is necessary to analyze the human gait cycle in the process of human dynamic recognitio. However, only a few works provided good results of each movement cycle [36]. Our data through periodic analysis and time axis comparison, which can be a good judgment and identification to identify knee joint motions.…”
Section: Identification Of Climbing and Descending Steps Of The Knee ...mentioning
confidence: 96%
“…It is necessary to analyze the human gait cycle in the process of human dynamic recognitio. However, only a few works provided good results of each movement cycle [36]. Our data through periodic analysis and time axis comparison, which can be a good judgment and identification to identify knee joint motions.…”
Section: Identification Of Climbing and Descending Steps Of The Knee ...mentioning
confidence: 96%
“…Guides or cues by some stimulus applied to the plantar region to increase the clearance in lower cadence individuals through the insole, could lead to the development of a smart insole that can prevent falls during gait. A study using tactile stimuli reported that when a small hemispherical protrusion was taped to the heel and the participants were instructed to step on the protrusion when the heel touches the floor, the ankle dorsi-flexion during heel strike and clearance during the swing phase increased [ 9 ]. This could also be applied to insoles; if a projection is attached to the heel of the insole and the individual attempts to land on the heel while stepping on a projectile, the insole will for prevent falls.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the previous study by Okoba at al. [ 9 ] revealed that when a small hemispherical protrusion was taped to the hallucal area, and the participants were instructed to walk placing the body weight on the protrusion seal during the kicking-out motion of the stride, increased plantar-flexion angle at terminal stance phase and increased plantar-flexor muscle (gastrocnemius) activity was observed.…”
Section: Introductionmentioning
confidence: 99%